Reclassification of the doryctine tribe Rhaconotini (Hymenoptera, Braconidae) - Belokobylskij, Sergey A.; Zaldívar-Riverón , Alejandro (European Journal of Taxonomy, 2021)
The classification of the genera belonging to the doryctine tribe Rhaconotini (Braconidae) is updated. The following new taxa are described: Troporhaconotus gen. nov. (with 12 species), Afroipodoryctes subgen. nov. (of Ipodoryctes Granger, 1949) (with three species), Hexarhaconotinus subgen. nov. (of Rhaconotinus Hedqvist, 1965) (with ten species), Bathycentor zimbabwensis sp. nov., Ipodoryctes (Afroipodoryctes) reunionus sp. nov., I. (A.) saintphilippensis sp. nov., Platyspathius (Platyspathius) venezuelicus sp. nov., P. (P.) ranomafanus sp. nov., Rhacontsira haeselbarthi sp. nov., Rh. mozambiquensis sp. nov., Rh. saigonensis sp. nov. and Rh. toamasina sp. nov. The generic status of Euryphrymnus Cameron, 1910 is resurrected. The generic name Aptenobracon Marsh, 1965 is synonymised under Rhaconotus Ruthe, 1854 (syn. nov.); Rhaconotus asiaticus Belokobylskij, 1990 is synonymised under Rh. kerzhneri Belokobylskij, 1985 (syn. nov.). The new name, Rhaconotinus austrochinensis nom. nov., is suggested for the preoccupied name Rhaconotus chinensis Chen & Shi, 2004 (December) not Rhaconotus chinensis Belokobylskij & Chen, 2004 (June). New species contents, in many cases with numerous new combinations, are suggested for the genera Bathycentor Saussure, 1892, Euryphrymnus Cameron, 1910, Ipodoryctes Granger, 1949, Rhaconotinus Hedqvist, 1965 and Rhaconotus. The tribe Leptorhaconotini is synonymised with Rhaconotini based on previously published molecular phylogenetic studies, though we leave this group within the subtribe Leptorhaconotina.